Incidence and Short term Outcome of Management of Neonatal Intestial Obstructin (NIO) - Atef Abd hamid Ekiabi; Mohamed El sayed Eraki (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2017)
Introduction: Neonatal intestinal obstruction (NIO) is a challenging and common emergency situation in pediatric surgery. In order to successfully manage it one should make a timely diagnosis and apply standard treatment.Management of neonatal intestinal obstructions have improved in many developed countries, but still show high morbidity and mortality in developing countries. This study was done to evaluate the incidence and short term outcome of neonatal intestinal obstruction at the department of pediatric surgery, Zagazig university hospitals in Egypt. Material and Methods: This retrospective study included 84 patients whom presented with intestinal obstruction during their first month of life to the emergency departments of Zagazig university hospitals in Egypt from Jan 2008 to Jan 2011and were managed surgically. Results: Of these 84 patients 50 were males and 34 were female. The mean age at presentation was 3.5 (2-10) days for duodenal atresia, 2.5 (3-5) days for jejunoileal  atresia , 2 (1-10) days for meconium ileus with perforation, 2 (1-5) days for patients with volvulus, 7 (5-20) days for colonic atresia, 20 (10-30) days for Hirschsprung disease, 25 (5-30) days for patients with obstructed congenital inguinal hernia and 2 (1-4) days for anorectal malformations. Surgery was done for all patients after resuscitation. Death occurred in 10 patients (12%). In 3 patients with jejunoileal atresia anastomotic leakage occurred; they underwent re-operation but died. In 3 patients with duodenal atresia death occurred postoperatively from sepsis and DIC. Two patients with high anorectal malformations died 2 days post operative from associated cardiac anomalies and 2 patients with colonic atresia died post operatively from sepsis and electrolyte imbalance. Conclusion: The most common cause of intestinal obstruction in neonates in our study was anorectal malformations and obstructed congenital inguinal hernia. Mortality and morbidity is still high compared with statistics from developed countries due to late presentation to pediatric surgeon and there is no specific neonatal surgical intensive care unit beside the pediatric surgery department in our center.